Alternative approach to variable wavelength interferometry - Litwin, Dariusz; Radziak, Kamil; Galas, Jacek (Photonics Letters of Poland, 2020)
The paper presents an alternative technique of calculation the retardance of quartz waveplates. The technique utilizes continuously tuned wavelength, which identifies the zero-order fringe and simultaneously facilitates high repeatability of the optical path difference across the entire visible spectrum. Unlike in classical method, precise monitoring of the current increase or decrease of the interference order is not required. The discussion includes comparison of the standard deviation between the classical and novel approaches. Full Text: PDF References M. Pluta, Advanced Light Microscopy (Vol. 3, PWN, Elsevier, Warszawa-Amsterdam-London-New York-Tokyo, 1993). DirectLink M. Pluta, "Object-adapted variable-wavelength interferometry. I. Theoretical basis", Journal of Opt. Soc. Am., A4(11), 2107 (1987). CrossRef M. Pluta, "Variable wavelength microinterferometry of textile fibres", J. Microscopy, 149(2), 97 (1988). CrossRef M. Pluta, "On double‐refracting microinterferometers which suffer from a variable interfringe spacing across the image plane", Journal of Microscopy, 145(2), 191 (1987). CrossRef M. Pluta, "Variable wavelength interferometry of birefringent retarders", Opt. Laser Technology, 19(3), 131 (1987). CrossRef D. Litwin, A. M. Sadik, "Computer-aided variable wavelength Fourier transform polarizing microscopy of birefringent fibers", Optica Applicata 28(2), 139 (1998). DirectLink A. Sadik, W. A. Ramadan, D. Litwin, "Variable incidence angle method combined with Pluta polarizing interference microscope for refractive index and thickness measurement of single-medium fibres", Measurement Science and Technology, IOP Publishing 14(10), 1753 (2003). CrossRef J. Galas, S. Sitarek; D. Litwin; M. Daszkiewicz, "Fringe image analysis for variable wavelength interferometry", Proc. SPIE 10445, 1044504 (2017). CrossRef D. Litwin, J. Galas, N. Błocki, "Automated variable wavelength interferometry in reflected light mode", Proc.SPIE 6188, 61880F (2006). CrossRef J. Galas, D. Litwin, M. Daszkiewicz, "New approach for identifying the zero-order fringe in variable wavelength interferometry", Proc. SPIE 10142, 101421R (2016). CrossRef D. Litwin, J. Galas, M. Daszkiewicz, T. Kryszczyński, A. Czyżewski, K. Radziak, "Dedicated optical systems of the Institute of Applied Optics", Phot. Lett. Pol., vol. 11, no. 2, pp. 29-31, (2019). CrossRef D. Litwin, K. Radziak, J. Galas "A fast variable wavelength interferometer", Proc. SPIE 11581, 115810O, (2020). CrossRef